Optimizing Insulin Delivery in Clinical Practice: Evidence-Based FITTER Guidelines for Improved Diabetes Management - Raina, Rohit; Dhoat, Preeti Singh; Chaudhary, Deepak; Singh, Rajat (Medicine Essentials in Clinical Practice, 2025)
Insulin delivery methods play a pivotal role in the management of diabetes mellitus. Subcutaneous injections remain the cornerstone of insulin administration, offering flexibility with different insulin types—rapid-acting, short-acting, intermediate-acting, and long-acting, tailored to individual patient needs. Insulin pens provide a convenient alternative, offering prefilled cartridges or disposable units that simplify dosing and enhance patient adherence. For patients requiring intensive insulin therapy, insulin pumps offer continuous subcutaneous infusion, delivering basal insulin throughout the day with bolus doses at meal times. These devices provide flexibility in dosing and lifestyle management, although they require regular monitoring and maintenance. Implantable insulin pumps, though less common, provide continuous insulin infusion via surgically placed devices under the skin. They enhance predictability and flexibility in insulin therapy, reducing the risk of hypo- and hyperglycemia. Continuous glucose monitoring (CGM) systems complement insulin delivery methods by providing real-time glucose readings, and facilitating personalized insulin adjustments based on glucose trends. Selecting the appropriate insulin delivery method is pivotal in diabetes management, considering patient preferences, lifestyle factors, and treatment goals. Tailored approaches ensure optimal glycemic control and improve quality of life for individuals with diabetes mellitus. This chapter provides an overview of various insulin delivery methods utilized in clinical practice. It highlights various delivery options, including subcutaneous injections, insulin pens, and pumps, tailored to individual patient needs. The FITTER guidelines, developed through a rigorous review of international practices and evidence, address key challenges such as needle reuse, lipohypertrophy, and patient adherence.